Dissolved organic matter characteristics and bacteriological changes during phosphorus removal using ladle furnace slag - Noh, Jin H.; Lee, Sang-Hyup; Choi, Jae-Woo; Maeng, Sung Kyu (TECHNO-PRESS, 2018)
A sidestream contains the filtrate or concentrate from the belt filter press, filter backwash, and supernatant from sludge digesters. The sidestream flow, which heads back into the sewage treatment train, is about 1-3% less than the influent flow. However, the sidestream can increase the nutrient load since it contains high concentrations of phosphorus and nitrogen. In this study, the removal of PO4-P with organic matter characteristics and bacteriological changes during the sidestream treatment via ladle furnace (LF) slag was investigated. The sidestream used in this study consisted of 11-14% PO4-P and 3.2-3.6% soluble chemical oxygen demand in influent loading rates. LF slag, which had a relatively high Ca2+ release compared to other slags, was used to remove PO4-P from the sidestream. The phosphate removal rates increased as the slag particle size decreased 19.1% (2.0-4.0 mm, 25.2% (1.0-2.0 mm), and 79.9% (0.5-1.0 mm). The removal rates of dissolved organic carbon, soluble chemical oxygen demand, color, and aromatic organic matter (UV254) were 17.6, 41.7, 90.2, and 77.3%, respectively. Fluorescence excitation-emission matrices and liquid chromatography-organic carbon detection demonstrated that the sidestream treatment via LF slag was effective in the removal of biopolymers. However, the removal of dissolved organic matter was not significant during the treatment. The intact bacterial biomass decreased from 1.64x10(8) cells/mL to 1.05x10(8) cells/mL. The use of LF slag was effective for the removal of phosphate, and the removal efficiency of phosphate was greater than 80% for up to 100 bed volumes.